ANALISIS KEBIJAKAN PEMANFAATAN CAGAR ALAM PULAU SEMPU, KABUPATEN MALANG, PROVINSI JAWA TIMUR - , ANDITA AULIA PRATAMA, Dr. Ahmad Maryudi, S.Hut., M.For. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Conservation areas have a vital role for biodiversity protection. In Indonesia, the gazettement of conservation areas refers to Law of the Republic of Indonesia No. 5/1990. Strict Nature Reserve according to this law is defined as a nature reserve area due to its nature conditions that have uniqueness of plants, animals, ecosystems or specific ecosystem that needed to be protected for the natural growth. According this definition, utilization and interference to these areas are strictly limited. However, tourism activities have steadily occurred in Sempu Island. This phenomenon may damage the strict nature reserve area and could inflict to nature resource and ecosystem conservation failures. This research aimed to: describe the gazettement policy of Sempu Island, describe the utilization and evaluate divergence levels of utilization activity of Sempu Island Strict Nature Reserve for the regulations. This research is qualitative research. In order to describe utilization dynamics, data and information were obtained through field observation, questionnaires, and interviews. Data analysis was done through historical approach and substance analysis which are processed through descriptive qualitative method. According to its characteristics, Sempu Island gazettement is in accordance to its gazettement policy. Dominant utilization in Sempu Island indicated to be recreational services in the form of tourism activities which have occurred in the early of year 2000s. Referring to policy substance analysis on strict nature reserve utilization, this activity is considered to be less appropriate to Sempu Island status as strict nature reserve. Therefore, it is necessary to review the utilization activity and gazettement status of Sempu Island Strict Nature Reserve.